Experience of nursing of integrated Traditional Chinese and western medicine for a patient undergoing repair of tissue defect after surgical treatment for oral and maxillofacial-head and neck carcinoma (1例口腔颌面头颈部肿瘤术后组织缺损修复中的中西医结合护理体会) - HUANG Hujing (黄慧静); WANG Yongling (王永灵); LIAO Mingjuan (廖明娟); LI Yan (李琰); KUI Gang (蒉纲) (Association of Integrative Nursing, 2022)
This paper summarized the experience of nursing of integrated Traditional Chinese and western medicine for a patient undergoing repair of tissue defect after surgical treatment for oral and maxillofacial-head and neck carcinoma. Key issues should be mentioned included close observation, standard wound-cleaning process, dressing change, moxibustion, rehabilitation exercise instruction, diet nursing and psychological nursing. The application of nursing of integrated Traditional Chinese and western medicine could improve the wound healing and relieve the negative emotion of the patient undergoing repair of tissue defect after surgical treatment for oral and maxillofacial-head and neck carcinoma. (本文总结1例口腔颌面头颈部肿瘤术后组织缺损修复中的中西医结合护理经验, 通过规范清理创面、科学换药, 配合中医艾灸、饮食指导、康复锻炼以及心理护理, 能有效缓解患者负性情绪, 促进创面愈合。)